IoT revolutionizes orchid cultivation in Indonesia with precision and efficiency: IoT merevolusi budidaya anggrek di Indonesia dengan presisi dan efisiensi - Bisri, Hasan; Syahrorini, Syamsudduha (Indonesian Journal of Innovation Studies, 2024)
The Orchidaceae family is highly valued in ornamental, perfume, medical, and cosmetic industries, but cultivation often fails due to human error. This research aims to design an IoT-integrated automation system to monitor and control key parameters such as air temperature, humidity, and moss moisture for orchid cultivation. Using the research and development method, we observed plant needs, reviewed relevant literature, designed an effective system, and tested sensor accuracy and system reliability. Results showed the DHT-22 sensor had a minimal error in temperature (0.9%) and humidity (2.1%) readings, and the soil moisture sensor had a 3.65% error. The system maintained optimal conditions, and the Blynk app effectively displayed data. This innovation reduces human error and enhances orchid cultivation efficiency, with potential applications in other sensitive plant systems. Highlight: Error Reduction: IoT system minimizes human error in orchid cultivation. Sensor Accuracy: DHT-22 sensors show minimal temperature (0.9%) and humidity (2.1%) errors. Optimal Conditions: Maintains air humidity 40%-80%RH and moss moisture 50%-80%RH. Keyword: Orchidaceae, IoT automation, sensor accuracy, environmental control, orchid cultivation